Plasma Glycosaminoglycans (GAGS) Levels as a Biomarker in Renal Cell Carcinoma Patients - Mumtaz, Hamayun; Aamir, Muhammad; Khalid, Usama Bin; Khan, Faraz Basharat; Bibi, Afshan; Haroon, Zujaja Hina (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the diagnostic accuracy of plasma Glycosaminoglycans (GAGs) in Renal Cell Carcinoma (RCC), taking histological findings as the reference standard.Study Design: Cross-sectional study.Place and Duration of Study: Department of Chemical Pathology and Endocrinology, Armed Forces Institute of Pathology, in collaboration with Armed Forces Institute of Urology, Rawalpindi Pakistan, from Sep 2020 to Jun 2021.Methodology: The study comprised sixty-two (62) diagnosed cases of RCC. All the patients had nephrectomy, and histopathological findings confirmed the diagnosis. Plasma samples for GAG levels were collected in EDTA tubes and assayed by manual ELISA. The Receiver Operating Characteristic (ROC) curve was constructed, and the Area Under the Curve (AUC) was calculated. Results: The mean age of the study population was 52.7+10.5 years. At a cut-off of 34 ng/ml, the sensitivity and specificity of plasma GAG levels were 83.9% and 94.2%, respectively, in diagnosing RCC taking biopsy as a gold standard. Positive predictive value (PPV) and negative predictive value (NPV) at this cut-off were 93.7% and 84.9% respectively. The area under the curve (AUC) for plasma GAG levels was 0.97, which further supported the use of this test in diagnosing RCC.Conclusion: Plasma GAG levels can be used as a promising diagnostic test in patients with RCC. It can prove relatively more convenient and cost-effective for diagnosing such cases.